From 2D Graphene Nanosheets to 3D Graphene‐based Macrostructures. Issue 19 (4th September 2020) - Mohd Firdaus, Rabita; Berrada, Nawal; Desforges, Alexandre; Mohamed, Abdul Rahman; Vigolo, Brigitte
Abstract: The combination of exceptional functionalities offered by 3D graphene‐based macrostructures (GBMs) has attracted tremendous interest. 2D graphene nanosheets have a high chemical stability, high surface area and customizable porosity, which was extensively researched for a variety of applications including CO2 adsorption, water treatment, batteries, sensors, catalysis, etc. Recently, 3D GBMs have been successfully achieved through few approaches, including direct and non‐direct self‐assembly methods. In this review, the possible routes used to prepare both 2D graphene and interconnected 3D GBMs are described and analyzed regarding the involved chemistry of each 2D/3D graphene system. Improvement of the accessible surface of 3D GBMs where the interface exchanges are occurring is of great importance. A better control of the chemical mechanisms involved in the self‐assembly mechanism itself at the nanometer scale is certainly the key for a future research breakthrough regarding 3D GBMs. Abstract : The assembly of nanomaterials such as graphene into 3D hierarchized nanostructures is definitely of great interest for a wide range of environmental applications. The idea of the present research is to transfer the properties of a super nanomaterial to a macroscopic material which should have its own properties multiplied.